Surgical versus conservative management of fifth metatarsal fractures in adults: A protocol of retrospective study - Qi, Rongfu (Medicine (Baltimore), 2020)
BACKGROUND: At present, the treatment of base fractures of the fifth metatarsal, especially the area I fractures, is still a controversial topic. The objective of our work was to assess the radiological and clinical outcomes of displaced avulsion fractures of the fifth metatarsal base after treated with conservative treatment or intramedullary screw. METHODS: All of the fifth metatarsal fractures patients underwent surgery by the senior authors in our hospital from January 2017 to December 2019 were reviewed. Institutional Review Board in the Subsidiary Hospital of Guizhou Medical University approved this study. Patients with the following conditions can be included: (1).. the displaced avulsion fracture of fifth metatarsal base; (2).. aged 18 to 40 years; (3).. a completed medical history; (4).. the patients were followed up for at least 6 months. Patients with the following conditions will be excluded: follow-up less than 6 months; open fracture; pathological fracture; osteoporotic fracture; patients have the history of ankle or foot surgery. Radiographs were taken at 1, 3, 6 and 12 months in outpatient follow-up. The following outcomes were assessed in the follow-up: functional outcomes, the score of patient satisfaction, as well as the motion range, and complications. All the statistical analyses were implemented via applying the software of SPSS Version 12 (SPSS Inc, Chicago, IL). RESULTS: We hypothesized that there was no remarkable difference between two groups in the outcomes after operation. TRIAL REGISTRATION: This study protocol was registered in Research Registry (researchregistry6024).